Prevalence and viral DNA loads of three novel human polyomaviruses in skin cancers from Japanese patients. Issue 8 (20th May 2013) - Imajoh, Masayuki; Hashida, Yumiko; Nakajima, Hideki; Sano, Shigetoshi; Daibata, Masanori
Abstract: Merkel cell polyomavirus (MCPyV), human polyomaviruses 6 (HPyV6) and 7 (HPyV7) are novel human polyomaviruses. This study investigated their detection rates and DNA loads in various skin cancers from Japanese patients. MCPyV, HPyV6 and HPyV7 were detected in 22.2%, 3.2% and 1.6% of squamous cell carcinomas, 18.0%, 2.0% and 4.0% of basal cell carcinomas, and 19.1%, 4.3% and 4.3% of melanomas, respectively. Quantitative real‐time polymerase chain reaction showed that their DNA loads were low. These findings provide the first evidence of the prevalence of HPyV6 and HPyV7 in skin cancers in Asia. Nucleotide differences were found in the large T‐sequenced region between Japanese and North American isolates: a nucleotide substitution of A to G for HPyV6; and a nucleotide substitution of T to C and the insertion of a gap for HPyV7. This suggested that two genotypes of HPyV6 and HPyV7 would be present and associated with geographical origin.